Precipitation variability, vegetation turnover, and anthropogenic disturbance over the last millennium in the Atacama highlands of northern Chile (19°S) - Domic, Alejandra I. (2023)
The Late-Holocene history of hydroclimatic variability in the Atacama Desert offers insights into the effects of precipitation and humans on ecosystems in one of the most extremely arid regions of the world. However, understanding the effects of regional precipitation variability in relation to local ecological stressors remains to be fully resolved. Here, we present a pollen-based qualitative precipitation reconstruction derived from fossil rodent middens recovered from two sites near Laguna Roja (LRO; n = 23) and Isluga (ISL; n = 14) in the Atacama highlands (19°S) of northern Chile. At LRO, the fossil pollen record shows multi-centennial hydroclimatic anomalies during the last millennium, with wetter than present phases at 1155–1130, 865–670, and 215–80 cal yrs BP, and similar to present conditions between 1005 and 880 cal yrs BP. In contrast, the ISL record shows a wet phase during 1115–840 cal yrs BP, suggesting that meso-ecological processes were as important in vegetation turnover as regional hydroclimate anomalies. Wetter conditions derived from LRO partially overlap with the Medieval Climate Anomaly (865–670 cal yrs BP) and with the latest part of the Little Ice Age (215–80 cal yrs BP). Furthermore, no strong anthropogenic signal was identified possibly related to the remote location of the records. Palynological diversity analyses evidence increasing diversification of plant communities during wet events at both sites. In correlation to existing regional hydroclimatic records from the Western Andes, our precipitation reconstruction verifies that centennial-scale changes in the strength of the South American Summer Monsoon (SASM) and partial influence of El Niño-like (ENSO) conditions drove vegetation turnover in the Atacama Desert during the last millennium.